Recurrent and/or metastatic thyroid cancer: therapeutic options. - Karavitaki, N; Vlassopoulou, V; Tzanela, M; Tzavara, I; Thalassinos, N (2002)
Thyroid cancer is relatively rare, accounting for 0.5 - 10 cases per 100,000 individuals per year. Despite their generally favourable prognosis, patients with differentiated thyroid cancer are at risk of tumour recurrence for decades after diagnosis. The optimal management remains controversial even in the low-risk patients because of the high cure rates, long natural history and rarity of these tumours. Therapeutic interventions in recurrent and metastatic differentiated thyroid cancer depend on the type of initial treatment, the site and the extent of disease. Surgical excision of the amenable-to-surgery lesions and radioiodine administration remain the first approach. External radiotherapy may be given to patients with inoperable lesions or those not concentrating radioiodine. Chemotherapy has not provided consistently successful results. Various therapeutic approaches for anaplastic carcinoma give poor results, making the development of novel treatments necessary. Innovative strategies, including recombinant human thyroid stimulating hormone, retinoic acid redifferentiation therapy and gene therapy, may lead to further improvement in the management of thyroid cancer arising from follicular cells.